Inherited metabolic epilepsies - Pearl, Phillip L. (Demos Medical Pub., 2013)
The explosion of information in neurogenetics and metabolism mandates increasing awareness of appropriate diagnostic and therapeutic strategies in the setting of certain epilepsies, especially those of very early onset. There are over 200 inherited disorders that are associated with seizures and prompt identification and intervention is crucial for a positive outcome. This text brings together the leading authorities working in this area to present state-of-the-art clinical reviews covering the science, recognition, and treatment of the inherited metabolic epilepsies and related disorders. The.